Effects of Varying Acupuncture Manipulations at ST36 (Zusanli) on Gastric Electrical Frequency and Amplitude in Bradygastria Rabbits. (9th March 2020) - Wang, Kang; Xu, Yuan; Niu, Yan; Liu, Yangyang; Lai, Hezheng; Xu, Zhifang; Zhang, Kuo; Guo, Yongming; Guo, Yi
Abstract : Objective. To observe the effects of different manual acupuncture (MA) manipulation on gastric electrical amplitude and frequency for noradrenaline-induced bradygastria in rabbits. Methods . A total of 60 rabbits were randomly allocated into six groups: four MA manipulation groups; reinforcing by twisting the manipulation group (FTG), reducing by twisting the manipulation group (RTG), reinforcing by lifting and thrusting the manipulation group (FLG), and reducing by lifting and thrusting the manipulation group (RLG), a control group (CG), and a model group (MG). The total treatment time length was 45 minutes. The bradygastria was induced via administration of noradrenaline via the marginal ear vein of the rabbits at 5 minutes from baseline, and the bradygastria model was established at 12 minutes from baseline. The rabbits in the four MA manipulation groups received different stimulation parameters at ST36 (Zusanli) for a duration of 3 minutes in accordance with their respective group allocation. The needles were then retained without further manipulation for a further 25 minutes. Gastric electrical amplitude and frequency were recorded using a data acquisition system (Biopac System MP150) at five different time points: baseline (for a duration of 5 minutes), after the bradygastria model was established at 12 minutes from baseline (for a duration of 5 minutes), during MA manipulation commencing at 17 minutes from baseline (for a duration of 3 minutes), 5 minutes after MA manipulation at 25 minutes from baseline (for a duration of 5 minutes), and at 20 minutes following MA manipulation at 40 minutes from baseline (for a duration of 5 minutes). Results . After noradrenaline induction, gastric electrical frequency levels in MA and MG groups were significantly decreased compared to the CG group (P < 0.05 ). However, there were no significant changes to gastric electrical amplitude (P > 0.05 ). During MA manipulation, gastric electrical frequency levels in RTG, FLG, and RLG groups were higher than in the MG group (P < 0.05 ). At 5 minutes after MA manipulation, gastric electrical frequency levels in RTG and FLG groups were higher than in the MG group (P < 0.05 ), and gastric electrical frequency level in the RTG group was higher than in the CG group (P < 0.05 ). At 20 minutes after MA manipulation, gastric electrical frequency levels in FTG, RTG, and FLG groups were higher than in the MG group (P < 0.05 ). Conclusion . All four variations of MA manipulations have a recovery effect on the gastric electrical frequency of rabbits with bradygastria. In particular, results indicated that FTG, RTG, and FLG at ST36 may have a regular and significant recovery trend through the whole process of the acupuncture intervention.